The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/jcla.24837
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus infection among pregnant women in the mountainous regions of southern China: A retrospective single‐center study

Abstract: Background Hepatitis B virus (HBV) infection remains a major public health issue worldwide. Moreover, its prevalence varies significantly in different geographic areas of China. The current study aimed to assess the prevalence of HBV infection among Hakka pregnant women in Meizhou, a remote mountainous region in southern China. Methods This research was performed between January 2015 and December 2020. In total, 16,727 pregnant women receiving antenatal care at Meizhou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
2
1
Order By: Relevance
“…A notable finding from this study is the unchanged prevalence or increasing trend in HBV infection among individuals aged over 35, similar to the observations in the study by Deng Q et al [ 22 ]. This phenomenon might be explained by the fact that individuals in this age group typically did not receive the HBV vaccine at birth or may have received it initially but experienced a decline in immunity over time, making them more susceptible to infection.…”
Section: Discussionsupporting
confidence: 91%
“…A notable finding from this study is the unchanged prevalence or increasing trend in HBV infection among individuals aged over 35, similar to the observations in the study by Deng Q et al [ 22 ]. This phenomenon might be explained by the fact that individuals in this age group typically did not receive the HBV vaccine at birth or may have received it initially but experienced a decline in immunity over time, making them more susceptible to infection.…”
Section: Discussionsupporting
confidence: 91%
“…The finding of this study 2.6% was higher than the results from studies conducted in Saudi Arabia 0.27% 26 , Iraq 1.1% 26 , Qater 1% 22 , Oman 1.49% 18 and in Russia 0.5 14 . On other hand, the results of the present study was lower than studies carried out in Jordan 5% 28 , Egypt 5% 27 , Sudan 5.6% 16 , Pakistan 5.2% 15 , Ethiopia 3.04 16 , Uganda 11.8% 29 , Greece 2.89% 13 and China 11.74% 10 . The result of this study reported that prevalence of HBV infection was lower than that studies conducted in the Yemeni capital in the years 2003, 2011 and 2013, which revealed that the seroprevalence among pregnant women were 3.8% 30 , 10.8% 21 .…”
Section: Discussioncontrasting
confidence: 87%
“…Vertical HBV transmission occurs if the mother has had acute HBV infection and most often occurs during the intrapartum period at the time of delivery 9 . Moreover, about 90% of infants born to mothers testing positive for hepatitis B surface antigens (HBsAg) or e antigens (HBeAg( will develop chronic infection which further develops to liver cirrhosis and hepatocellular carcinoma in young adulthood, posing a significant global public health challenge 10 . Parenteral transmission is still significant in developing countries and currently the most common method of transmission of HBV in developed countries 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The hepatitis B surface antigen (HBsAg) can be carried without causing any symptoms, or the condition can progress to severe, active variants that cause fibrosis, liver cirrhosis, and hepatocellular carcinoma (HCC) [4]. In Jordan, the prevalence of HBV among pregnant women is around 5% [6], which is less than in China and some African countries (6-11.7%) [7][8][9], but quite higher than in other Middle Eastern countries (1.5-4%) [10,11]. As vertical transmission is the main route for HBV infection among pregnant women, it could be prevented mainly by vaccination and antiviral treatment during pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%